Initiation of implementation of covid-19 tough workers and digital marketing expansion in sticker cutting business in Seduri Village, Mojokerto - Tri Mul Yono; Yudha Nurdian (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
At the Dheary Sicker company, there are various problems due to the Covid19 pandemic, in addition to decreasing their income, there is also a lack ofconcern for prevention regarding Covid- 19. This is a background for theholding of education regarding the application of health protocols in theworkplace because in the workplace many people go in and out to carry outeconomic activities. The method used in dealing with these problems is theThematic KKN Back To Village University of Jember with the Educationwork program regarding the rules of Health Protocol in the workplace suchas mandatory use of masks, washing hands, and maintaining a safe distance.In addition, to expand the market share in the cutting sticker business so thatit remains in the midst of the Covid pandemic, among others, by conductingonline promotions using digital sites such as WA and FB, and Shopee tomarket their products. Furthermore, regarding labeling training on productsand finally performance evaluation.